Pulmonary cavitations with increased 18F-FDG uptake revealing a thoracic endometriosis: A case report. Issue 42 (22nd October 2021) - Mulette, Pauline; Jacquet, Amaury; Durlach, Anne; Papathanassiou, Dimitri; Lalire, Paul; Graesslin, Olivier; Delepine, Gonzague; Dury, Sandra; Dormoy, Valérian; Perotin, Jeanne-Marie; Lebargy, François; Deslée, Gaëtan; et al.
Abstract: Rationale: Thoracic endometriosis is a rare disorder that can involve airways, pleura and lung parenchyma. It is the most frequent form of extra-abdominopelvic endometriosis. Multiple lung cavitations are a rare feature of thoracic endometriosis. Patient concerns: A 46-year-old woman was referred to our hospital after incidental finding of multiple pulmonary cavitations with surrounding areas of ground glass opacity on a thoraco-abdominal computed tomography-scan performed for abdominal pain. Retrospectively, the patient also reported mild hemoptysis occurring 4 months ago. Diagnoses: Positron emission tomography–computed tomography scan revealed moderate and homogeneous [ 18 F] fluoro-2-deoxy-D-glucose ( 18 F-FDG) uptake in pulmonary cavitations (maximum standardized uptake value 5.7). The diagnosis of thoracic endometriosis was confirmed by histological examination of surgical resection of a left lower lobe cavitation. Interventions and outcome: Gonadotropin-releasing hormone analogues associated with add-back therapy was started. Four months after initiating pharmacological treatment, the chest computed tomography-scan showed a dramatic decrease in lung cavitations size. Lessons: Thoracic endometriosis is a rare disorder requiring a multidisciplinary management including gynaecologist, pulmonologist, radiologist, nuclear physician, pathologist and thoracic surgeon for early diagnosis and treatment. Our case report highlights that an increased 18 F-FDG uptake can be found in thoracic endometriosis syndrome presenting as multiple lung cavitations.